Conflictos de usos del suelo como aporte a la sostenibilidad agroproductiva de los lotes 3, 4 y 5 de CIIDEA - Hernández González, Jamilex Karey (2024)
The objective of the research was to assess land use conflicts and their impact on agro-productive sustainability in lots 3, 4 and 5 of CIIDEA of ESPAM MFL in Manabí, Ecuador. The methodology of the study included field visits and mapping data collection with drone and GPS to obtain high-resolution images and geographical coordinates of land uses and land covers. This was complemented with the collection of soil samples to determine their current use capacity. From these data, a spatial analysis was carried out to identify land use conflicts. Geographic information layers of capacity and coverage were overlaid to identify areas of land conflict. The study revealed a balanced distribution of land cover, with 35% natural vegetation, 25% grassland, 20% crops and 20% native forest. The land use capacity showed that 40% has a high capacity for agricultural and livestock activities, 30% medium capacity and 30% low capacity. It also revealed that approximately 46% of the soils had underutilisation conflicts, while 23% had over utilisation conflicts and the remaining 31% had adequate land use. The resulting conflicts compromise agro-productive sustainability and the resilience of soil ecosystems. In conclusion, the research highlights the need to address land use conflicts in the studied plots to ensure agro-productive sustainability.